Location Based Service Technology in Mapping Tourism Potential with a Combination of AHP and Profile Matching Methods - Veny Cahya Hardita; Sherly Jayanti; Normalia Normalia (Prodi Ilmu Komputer Universitas Bumigora, 2023)
Background: Palangkaraya is a city that has a variety of natural beauty and culture. However, the tourism potential in this area is still not fully optimized and managed properly. One of the causes of this is the lack of ownership by the Government regarding the mapping of areas that have the potential to become tourist areas in Palangkaraya City. Therefore a system is needed that can assist the Government in mapping areas that have the potential to become tourist areas Objective: Develop a system that can be used to map areas that have the potential to become tourist areas. The information generated from the developed system is expected to assist the government and the private sector in increasing tourism in Palangkaraya City. Methods: The method used is the application of Location Based Service technology with a combination of Analytical Hierarchy Process and Profile Matching methods. Result: The system developed uses 10 criteria with 37 alternatives to produce information related to the sequence of tourism potential levels where the results of the sequence are then displayed on a map to provide an overview of the mapping of tourism potential areas. Conclusion: The system that has been created has succeeded in mapping areas that have tourism potential by applying LBS technology and a combination of AHP and Profile Matching methods. From this system it was found that blood with the alternative code A1 had the highest value, namely 4.295193, followed by A10 with a value of 4.156934 and so on. The test results were carried out by comparing the results of the system with the calculation results, it was found that the results were appropriate.